1986
DOI: 10.1002/aic.690320310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surfactants on mass transfer during spray drying

Abstract: A study was conducted to investigate the effects of added surfactants on mass transfer during spray drying. Measurements were made of retention of volatile components and amount of water evaporation at various points near the atomizer inside a spray dryer of pilot plant scale. Experimental data indicate that surfactants can have a substantial effect on transport processes when certain types of liquid solutions are spray dried. Experimental results are interpreted in terms of transport mechanisms and are compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…It is plausible that given sufficient cumulative contact time, protein molecules will form large aggregates and become insoluble, but those having short overall contact time will form dimers and remain soluble. Polysorbate molecules not only occupy the interface but also slow the fluid movement in the droplets, [24][25][26] thereby reducing the chance for rhGH molecules to be denatured at the interface. These two factors caused by surfactant reduce the contact time of rhGH molecules with the interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that given sufficient cumulative contact time, protein molecules will form large aggregates and become insoluble, but those having short overall contact time will form dimers and remain soluble. Polysorbate molecules not only occupy the interface but also slow the fluid movement in the droplets, [24][25][26] thereby reducing the chance for rhGH molecules to be denatured at the interface. These two factors caused by surfactant reduce the contact time of rhGH molecules with the interface.…”
Section: Resultsmentioning
confidence: 99%
“…One speculation as to how surfactant might smooth out the surface is that the presence of surfactant reduces internal motions and surface turbulence of the droplets during drying. [24][25][26] However, whether reducing the flow motion of the droplets would minimize the formation of a raisin-like surface has yet to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, if one component is surface-active, the formation of an insoluble monolayer at the interface can reduce the evaporation rate by introducing an interfacial resistance to mass transfer. Frey and King (1986) showed that surfactants can have a substantial effect on mass transfer in spray drying. All of these complications will be examined herein.…”
Section: = Hi2)(a) [Majn(ma)]' -J(ma) [ a H 3 A ) ] 'mentioning
confidence: 99%
“…The necking phenomena with subsequent detachment occurs in sprays also and should impart oscillation and unsteady internal flow. This may explain the results of Frey and King (1986), who found higher mass transfer rates than those predicted by the Kronig and Brink model. Also, models that predict velocity-dependent mass transfer coefficients do not explain the experimental data.…”
Section: Discussionmentioning
confidence: 73%